Anti-islanding techniques for Inverter-based Distributed Generation systems - A survey - Guha, Bikiran; Haddad, Rami J.; Kalaani, Youakim (SoutheastCon 2015, 2015)
The increased penetration of Inverter-based Distributed Generation (DG) in Smart Grid systems requires an adequate level of monitoring and detection especially under islanding conditions. Islanding occurs when a DG system is disconnected from the rest of the power grid. These DG systems are usually independently owned and controlled, thus when islanding occurs, the electric utility loses control and supervision over that section of the power grid. As a consequence, islanding can present serious safety hazard since a presumed disconnected power line can still unexpectedly be fed by nearby DG sources. Furthermore, prolonged islanding can also prevent reconnection to the power grid and may cause damage due to voltage and frequency excursions. Therefore, islanding detection, which is also called "Anti-Islanding", is one of the most critical aspects of the integration of DG sources into the power grid. There has been considerable research on developing detection techniques, however, recent breakthroughs in this field have resulted in significant modifications to the Anti-Islanding taxonomy which is the subject of this investigation. In this paper, a comprehensive survey was conducted with the objective of highlighting the latest Anti-Islanding techniques presented in the literature. Extensive comparisons of improvements and limitations of these new techniques was provided. Finally, open research areas in this field were identified.